Student Comprehension of Primary Literature is Aided by Companion Assignments Emphasizing Pattern Recognition and Information Literacy. - Sarah Shannon; Brian Winterman (Issues in Science and Technology Librarianship, 2012)
Primary literature is our main mode of communication in the sciences. As such, it is important for our undergraduates in the discipline to learn how to read primary literature. Incorporating primary literature into undergraduate science courses is often difficult because students are unprepared to comprehend primary articles. Learning to read and evaluate primary literature can improve students' understanding of science and the scientific method, and develop the educational and life skill of evaluating whether assertions are supported by evidence. We integrated two areas of research (teaching students to use primary literature and pattern recognition in experts versus novices) to modify a curriculum used to teach information literacy and primary literature in an introductory biology course. The modifications taught students to recognize information by the communication patterns used in the literature, and despite literature's jargon. One section of this course used our modified curriculum while two control sections used the original curriculum. In all sections, students were asked to write a lab report citing a primary literature article pertinent to their laboratory experiment. We read each lab report and the article it cited, ranking the student's comprehension of the article and their ability to integrate the article into their laboratory report on a scale of 1 to 3 using rubrics. While citing a primary literature article was required of all students, more students using the modified curriculum cited primary articles in their laboratory reports (95% vs. 65% average in control sections). The comprehension of primary articles also appeared better, as cited articles were more likely to be correctly paraphrased by students with the modified curriculum (average score of 2.33 vs. 1.96), while there did not appear to be a difference between the groups' abilities to integrate the article into their report. This indicates that by incorporating pattern recognition assignments and information literacy instruction into the curriculum, teachers can significantly improve student comprehension of primary literature. [ABSTRACT FROM AUTHOR]